Drainage Network Performance Mapping in the Tukad Ngenjung Sub-System Based on Geographic Information Systems (GIS) - Ardana, Putu Doddy Heka; Santika, Ketut Puspa (Journal of Information System, Technology and Engineering, 2024)
The aim of this research is to determine the condition and performance of the drainage network. The method used in this research is a quantitative descriptive method based on field observations. The results of this research based on hydrological and hydraulic calculations show that in the Tukad Ngenjung Sub System drainage network, out of a total of 52 channels, 42 channels are unable to accommodate the design flood discharge with a return period of 2 years and there are 45 channels that are unable to accommodate the design flood discharge with a 5 year return period. For channels that are unable to accommodate flood discharge, the design should be given more attention or repairs should be carried out by the relevant parties, so that the runoff that occurs in the channel can be resolved.